Soybean Yield and Nutrition Grown on the Straw of Grain Sorghum Inoculated with Azospirillum brasilense and Intercropped with BRS Paiaguás Grass - Soares, Deyvison de Asevedo; Modesto, Viviane Cristina [UNESP]; Nakao, Allan Hisashi [UNESP]; Soares, Wellington Rosa; Freitas, Leandro Alves [UNESP]; Dickmann, Lourdes [UNESP]; Pascoaloto, Isabô Melina [UNESP]; Andreotti, Marcelo [UNESP] (MDPI, 2023)
The adoption of diversified agricultural systems that employ integrated cultural practices appears to be the way to sustainably intensify tropical agriculture. Our objectives were to evaluate the dry matter (DM) accumulation of sorghum inoculated with Azospirillum brasilense, with or without a nitrogen fertilization split, intercropped with palisade grass (Urochloa brizantha cv. BRS Paiaguás), and how these practices influenced the nutrition and development of soybean in succession. The design was a randomized complete block in a 2 × 2 × 3 factorial, consisting of sorghum monoculture cropped or intercropped with palisade grass, sorghum either inoculated or not with A. brasilense, and nitrogen applied at 120 kg ha−1 N only at sowing, only at topdressing, or split—30% at sowing and 70% at topdressing at the beginning of the panicle initiation stage. The residual impacts of these treatments on the following soybean crop were also evaluated. Higher DM yield occurred in sorghum inoculated with A. brasilense, however, this result varied by year. The sorghum–palisade grass intercrop produced a higher amount of straw than sorghum monoculture. The nutrition of soybean was adequate regardless of treatments, but grain yield was higher when the sorghum residue was inoculated. The inoculation of A. brasilense in sorghum intercropped with palisade grass increased yield. The nutrition of soybean was adequate regardless of the treatments, while grain yield was higher on the inoculated sorghum residues. The inoculation of A. brasilense in sorghum intercropped with palisade grass increased DM yield. The intercropping increased the production of biomass for animal grazing and DM for soil coverage. The inoculation of sorghum by A. brasilense and its intercropping with palisade grass contributed to higher soybean yield in succession.
Keywords: Glycine maxL; grain yield; intercropping; soil fertility; Sorghum bicolor L. Moench